Preventive role of community-level social capital in the need for long-term care and impairment in instrumental activities of daily living: a multilevel analysis - Hitomi Matsuura; Yoko Hatono; Isao Saito (Komiyama Printing Co. Ltd, 2023)
Background: Individual-level social capital is an important determinant of older adults' long-term care needs; however, there is scant evidence regarding community-level social capital. Therefore, we investigated the association between community-level social capital and the prevalence of the need for long-term care among older adults. Methods: Between January and February 2018, a cross-sectional survey was conducted among all older adults (n = 13,558) aged 65 to 74 years in a rural municipality in Japan (total population, n = 72,833). A self-reported questionnaire was used to identify community-level social capital, comprising civic participation, social cohesion, and reciprocity. A multilevel logistic regression analysis was performed to estimate the odds ratios of the need for long-term care and a decline in social activity competence as assessed by instrumental activities of daily living. For the analysis, the community levels were divided into 76 voting districts and adjusted for daily life, lifestyle, socioeconomic status, health conditions, and the three social capital subscale scores at the individual level. Results: After adjusting for the covariates, we observed a tendency that a higher community level of reciprocity was associated with a lower prevalence of long-term care needs (OR: 0.86, 95% confidence interval: 0.75-1.00), whereas a high community level of social cohesion was associated with a significantly reduced decline in instrumental activities of daily living (OR per standard deviation increase: 0.87, 95% confidence interval: 0.79-0.96). No significant association was found with civic participation. Similarly, individual-level social capital was associated with the need for long-term care and decline in instrumental activities of daily living. Conclusions: Our findings suggest that good community-level reciprocity or social cohesion as well as good individual social capital status may help prevent the need for long-term care among older adults.